Rare and potentially fatal: cytogenetically cryptic TNIP1::PDGFRB and PCM1::FGFR1 fusion leading to myeloid/lymphoid neoplasms with eosinophilia in children - Berking, Ann-Cathrine; Flaadt, Tim; Behrens, Yvonne Lisa; Yoshimi, Ayami; Leipold, Alfred; Holzer, Ursula; Lang, Peter; Quintanilla-Martinez, Leticia; Schlegelberger, Brigitte; Reiter, Andreas; Niemeyer, Charlotte; Strahm, Brigitte; et al. (Cancer genetics, 2023)
Myeloid/lymphoid neoplasms with eosinophilia (MLN-eos) are rare haematological neoplasms primarily affecting adults. The heterogeneous clinical picture and the rarity of the disease, especially in children, may delay an early diagnosis. MLN-eos are characterized by constitutive tyrosine kinase (TK) activity due to gene fusions. It is thus of importance to obtain a prompt genetic diagnosis to start a specific therapy. Here, we outline the clinical, genetic, and biochemical background of TK driven MLN-eos and report two extremely rare paediatric cases of MLN-eo, the used diagnostic methods, therapy and clinical outcomes. Our results demonstrate that, standard cytogenetic and molecular methods may not be sufficient to diagnose MLN-eo due to cytogenetically cryptic aberrations. We therefore recommend performing additional evaluation with fluorescence in-situ hybridization and molecular genetic methods (array-based comparative genomic hybridization and RNA sequencing) which will lead to the correct diagnosis. Following this diagnostic route we detected a TNIP1::PDGFRB and a PCM1::FGFR1 fusion in our patients. Thus, genetic diagnosis must be precise and quick in order to initiate adequate therapies with tyrosine kinase inhibitors or HSCT.